Existentialism Theology: Christian Existentialism and Human Existence in Theological Context Understanding The Meaning of the Transcendental - Pranatha, Loudy Benedictus; Willyam, Verry; Waoma, Ken Jacks Gunawan (Institut Agama Kristen Negeri Toraja, 2025)
This article aims to explore the intersection between existentialist philosophy and Christian theology, particularly in understanding the limits of human existence and the role of transcendence. It highlights how existentialist themes such as freedom, responsibility, and individuality contribute to a deeper understanding of faith and the human condition. By examining the thoughts of key existentialist thinkers such as Søren Kierkegaard, Jean-Paul Sartre, Paul Tillich, and Karl Theodor Jaspers, the study analyzes their relevance within the framework of Christian faith. Furthermore, it discusses how individuals seek meaning in life amidst uncertainty and existential emptiness, and how transcendental experiences can offer a sense of purpose beyond mere religious formality. Using a qualitative method through a library research approach, this article presents a theological perspective on existentialism. Ultimately, it argues that engaging with existentialist thought can enrich theological reflection and foster meaningful dialogue between existentialism and theology in addressing the profound questions of human existence.